Threat of Punishment Motivates Memory Encoding via Amygdala, Not Midbrain, Interactions with the Medial Temporal Lobe - Murty, V. P.; LaBar, K. S.; Adcock, R. A. (The Journal of neuroscience, 2012)
Neural circuits associated with motivated declarative encoding and active threat avoidance have both been described, but the relative contribution of these systems to punishment-motivated encoding remains unknown. The current study used functional magnetic resonance imaging in humans to examine mechanisms of declarative memory enhancement when subjects were motivated to avoid punishments that were contingent on forgetting. A motivational cue on each trial informed participants whether they would be punished or not for forgetting an upcoming scene image. Items associated with the threat of shock were better recognized 24 h later. Punishment-motivated enhancements in subsequent memory were associated with anticipatory activation of right amygdala and increases in its functional connectivity with parahippocampal and orbitofrontal cortices. On a trial-by-trial basis, right amygdala activation during the motivational cue predicted hippocampal activation during encoding of the subsequent scene; across participants, the strength of this interaction predicted memory advantages due to motivation. Of note, punishment-motivated learning was not associated with activation of dopaminergic midbrain, as would be predicted by valence-independent models of motivation to learn. These data are consistent with the view that motivation by punishment activates the amygdala, which in turn prepares the medial temporal lobe for memory formation. The findings further suggest a brain system for declarative learning motivated by punishment that is distinct from that for learning motivated by reward.